RF energy harvesting based relays : non-orthogonal AF vs dynamic DF - Rao, Yepuri Sudhakara (2020)
A relay-based system, where the relay node is powered by radio frequency (RF) based energy harvesting (EH), has been considered. This work characterizes the diversity-multiplexing tradeoff (DMT) of non-orthogonal EH based amplify-and-forward (EH-NAF) protocol. Analysis of the protocols reveals that its DMT performance approaches that of non-EH based counterpart for smaller energy harvesting durations. Finally, EH-NAF is compared with EH based dynamic decode- and-forward (EH-DDF) protocol.